Analisis Erosi Terhadap Pengembangan Sistem Agroforestri pada Hutan Rakyat di Desa Lupia Kecamatan Kabangka Kabupaten Muna - Firman Syah; Eva Oktaviani; Hendra Kurniawan; Vellani Losenni Undra; Rosalia Silaban (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2025)
This research aims to analyze the level of erosion in various planting patterns of agroforestry systems implemented by the community in Lupia Village, Kabangka District, Muna Regency. The background of this research is based on the issue of land degradation due to population pressure on forest areas, which prompts the need for alternative approaches such as agroforestry. The research was conducted from June to July 2012 using field study and laboratory analysis methods. The collected data includes information on rainfall, slope, soil texture and structure, as well as the types of planting patterns used. The calculation of erosion rates was done using the USLE (Universal Soil Loss Equation) method. The research results show that the agroforestry planting pattern consisting of a combination of Teak-Banana-Papaya (with an 8% slope) produced the lowest erosion rate of 17.40 tons/ha/year, while the combination of Teak-Long Beans-Cocoa (with a 12% slope) showed the highest erosion rate of 34.31 tons/ha/year. All observed planting patterns resulted in erosion levels exceeding the tolerance threshold, thus not reflecting a sustainable system. Therefore, it is necessary to apply soil conservation techniques to support the sustainability of the agroforestry system in the area.